All-Inside, All-Epiphyseal Autograft Reconstruction of the Anterior Cruciate Ligament in the Skeletally Immature Athlete - Fabricant, Peter D. (JBJS Essent Surg Tech, 2013)
INTRODUCTION: We present an all-inside, all-epiphyseal anterior cruciate ligament (ACL) reconstruction technique with use of a hamstring autograft for skeletally immature athletes. STEP 1: IDENTIFY SUBCUTANEOUS LANDMARKS: Identify and mark subcutaneous landmarks to aid with anatomic orientation throughout the operation and to assist with socket placement. [Figure: see text] STEP 2: HARVEST THE HAMSTRING GRAFT: Harvest a hamstring autograft to create a four-strand autograft in the standard fashion or, if you prefer, perform a posterior hamstring harvest. STEP 3: PREPARE THE GRAFT: Prepare a four-strand hamstring autograft using suspensory cortical fixation devices—a reverse-tensioning button (ACL TightRope RT; Arthrex, Naples, Florida) on the femoral side and an attachable button system (ACL TightRope ABS, Arthrex) on the tibial side. [Figure: see text] STEP 4: PREPARE THE FEMORAL AND TIBIAL SOCKETS: Create blind-ended intra-articular sockets in the femur and tibia using the center-center footprint positions while avoiding the physeal plates. [Figure: see text] [Figure: see text] STEP 5: PASS AND SECURE THE GRAFT: Pass the hamstring autograft through the anteromedial portal and dock it in the femoral and tibial sockets; engage the cortical button on the femur, dock the graft, and then perform final fixation on the tibial side. [Figure: see text] [Figure: see text] STEP 6: POSTOPERATIVE REHABILITATION: The patient’s age and maturity level dictate the progression of rehabilitation, and parents and caregivers are encouraged to regularly participate in the child’s rehabilitation regimen. RESULTS: Research is ongoing to evaluate the clinical and radiographic outcomes following ACL reconstruction in skeletally immature athletes with use of this technique(19). WHAT TO WATCH FOR: Indications Contraindications Pitfalls & Challenges